Hubungan Sistem Pengurusan Sekolah Kualiti (SPSK) dengan kualiti dan produktiviti guru di Sekolah Rendah Rintis daerah Johor Bahru - Abdul Rahman, Abd. Rahim (2012)
This descriptive research aims to identify the relationship between Quality School Management System and teacher’s productivity and quality. A total of 56 school administrators consisting of Headmasters and Senior Assistant Teachers from 14 pilot primary schools in the Johor Bahru were involved. Data from the 2011 Verification Summary Report were used to examine the level of Quality School Management System, while the survey instrument developed by Rahmah (1997) was used to identify teacher’s level of productivity and quality. The finding of the pilot study indicated that the instrument’s coefficient alpha is 0.966. Data from the survey were analysed using the Statistical Package of Social Sciences (SPSS) version 14.0, involving descriptive and inferential statistics of correlation only. Findings of the study show that the Quality School Management System is highly practised with five dominant aspects, which are Management of Timetable, Teaching and Learning, Student’s Work Review, Examination and Subject Panel. Meanwhile, the most dominant aspects of teacher’s productivity and quality are Personality, Knowledge, Leadership and Skills. The correlation analysis shows that there is no significant correlation between the level of Quality School Management System and teacher’s productivity and quality. Finally, the study proposed several suggestions to relevant agencies or parties for further actions and for future research.